The organizational learning process in a agribusiness cooperative central - Royer, Douglas; Silva, Frederico Fonseca da; Jovtei, Estanislau Gonçalves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
To analyzing the process of organizational learning in central agribusiness cooperative in the light of OADI-SMM model, from the perspective of the organization having cooperated as an individual, the study of construct left the following assumptions: understand the main concepts of learning organizational and OADI-SMM model; understand the peculiarities of cooperative organizations in agribusiness and its main features management; understand the process of organizational learning in central agribusiness cooperative, its main engines, agents and moments; analyzing the light of OADI-SMM model the process of learning in the unit of study and possible disruptions in organizational learning. With the interpretation of context and attention to detail and the experiences of respondents, it can be concluded in the study that, over time, the Central Cooperative has developed and strengthened continuously and endemically their organizational learning mechanisms and as a way to cope with the complexity of agribusiness, has been able to promote the exchange of knowledge acquired in adaptations to the environment. The main finding of this case study is that the Central Cooperative can promote the transfer of learning between the individual and the organizational, so we really learn.